#TITLE_ALTERNATIVE# - MUSA (NIM 23299517), WAHAB
Any one who has developed an microelectronic system will have desired an oscilloscope for displaying the signal characteristic. The standard oscilloscope has an analog and digital type operations. To fulfill the digital oscilloscope requirements, the computer properties i.e. processor, storage, display and input/output can be used with some additional program for display, processing, and saving data measurment. Study about oscilloscope fundamental, some type of computer based oscilloscope, and digital oscilloscope implementations using sound card under Linux operating systems, have done in this research. Both hardware and control software would be tested, and it's functions work properly. The hardware capable for receive frequency input signal up to 4 MHz, but it's limited by CMI8738 stereo sound card 16-bit resolutions with the maximum frequency input is 20 kHz. Control software is implemented using GCC (GNU Compiler Collections) Linux tools and X-Window graphics tools and expected to operate as a dual trace oscilloscope for displying graphics signal input. The oscilloscope who implemented in this research named Xoscope made by Tim Witham, have two input channal who can operate simultaneously, and can be upgrade to eight input channal. Also the input signal can be attack to serial port via ProbeScope, Cat. No. 22-310 with frequency input up to 5 MHz. The prototype oscilloscope require future development to be operate like standard oscilloscope. The result of the research indicate that the deviations is 1.3 % from the actual signal. Measured verifications in amplitude and frequency to the CS-3026 oscilloscope produce a linearity relation with data measuring using Xoscope.